Modulation of Excitability of Stellate Neurons in the Ventral Cochlear Nucleus of Mice by ATP-Sensitive Potassium Channels - Bal, R.; Ozturk, G.; Önalan, E.O.; Him, A.; Cengiz, N.; Kuloǧlu, T.; Tuzcu, M. (Springer New York LLC barbara.b.bertram@gsk.com, 2018)
Major voltage-activated ionic channels of stellate cells in the ventral part of cochlear nucleus (CN) were largely characterized previously. However, it is not known if these cells are equipped with other ion channels apart from the voltage-sensitive ones. In the current study, it was aimed to study subunit composition and function of ATP-sensitive potassium channels (KATP) in stellate cells of the ventral cochlear nucleus. Subunits of KATP channels, Kir6.1, Kir6.2, SUR1, and SUR2, were expressed at the mRNA level and at the protein level in the mouse VCN tissue. The specific and clearly visible bands for all subunits but that for Kir6.1 were seen in Western blot. Using immunohistochemical staining technique, stellate cells were strongly labeled with SUR1 and Kir6.2 antibodies and moderately labeled with SUR2 antibody, whereas the labeling signals for Kir6.1 were too weak. In patch clamp recordings, KATP agonists including cromakalim (50 µM), diazoxide (0.2 mM), 3-Amino-1,2,4-triazole (ATZ) (1 mM), 2,2-Dithiobis (5-nitro pyridine) (DTNP) (330 µM), 6-Chloro-3-isopropylamino- 4H-thieno[3,2-e]-1,2,4-thiadiazine 1,1-dioxide (NNC 55-0118) (1 µM), 6-chloro-3-(methylcyclopropyl)amino-4H-thieno[3,2-e]-1,2,4-thiadiazine 1,1-dioxide (NN414) (1 µM), and H2O2 (0.88 mM) induced marked responses in stellate cells, characterized by membrane hyperpolarization which were blocked by KATP antagonists. Blockers of KATP channels, glibenclamide (0.2 mM), tolbutamide (0.1 mM) as well as 5-hydroxydecanoic acid (1 mM), and catalase (500 IU/ml) caused depolarization of stellate cells, increasing spontaneous action potential firing. In conclusion, KATP channels seemed to be composed dominantly of Kir 6.2 subunit and SUR1 and SUR2 and activation or inhibition of KATP channels regulates firing properties of stellate cells by means of influencing resting membrane potential and input resistance. © 2018, Springer Science+Business Media, LLC, part of Springer Nature.
Keywords: ATP-Sensitive Potassium Channels; Cochlear Nucleus; KATP; Stellate Cells